High-resolution mantle tomography of China and surrounding regions - Huang, Jinli; Zhao, Dapeng (Journal of Geophysical Research: Solid Earth, 2006)
A high‐resolution P wave tomographic model of the crust and mantle down to 1100 km depth under China and surrounding regions is determined by using about one million arrival times of P, pP, PP, and PcP waves from 19,361 earthquakes recorded by 1012 seismic stations. The subducting Pacific slab is imaged clearly as a high‐velocity zone from the oceanic trenches down to about 600 km depth, and intermediate‐depth and deep earthquakes are located within the slab. The Pacific slab becomes stagnant in the mantle transition zone under east China. The western edge of the stagnant slab is roughly coincident with a surface topographic boundary in east China. The active Changbai and Wudalianchi intraplate volcanoes in northeast China are underlain by significant slow anomalies in the upper mantle, above the stagnant Pacific slab. These results suggest that the active intraplate volcanoes in NE China are not hot spots but a kind of back‐arc volcano associated with the deep subduction of the Pacific slab and its stagnancy in the transition zone. Under the Mariana arc, however, the Pacific slab penetrates directly down to the lower mantle. The active Tengchong volcano in southwest China is related to the eastward subduction of the Burma microplate. The subducting Indian and Philippine Sea plates are also imaged clearly. The Indian plate has subducted down to 200–300 km depth under the Tibetan Plateau with a horizontal moving distance of about 500 km. High‐velocity anomalies are revealed in the upper mantle under the Tarim basin, Ordos, and Sichuan basin, which are three stable blocks in China.